A Web Tool for Consensus Gene Regulatory Network Construction - Sarkar, Chiranjib; Parsad, Rajender; Mishra, Dwijesh C.; Rai, Anil (Frontiers in Genetics, 2021)
Gene regulatory network (GRN) construction involves various steps of complex computational steps. Step-by-step procedure requires prior knowledge of programming languages such as R. Development of a web tool may reduce this complexity in the analysis steps and which can be easy accessible for user. In this study, a web tool for constructing consensus GRN by combining the outcomes obtained from four methods correlation, principal component regression, partial least square and ridge regression has been developed. We have designed the web tool with interactive and user friendly web page using php programming language. We have used R script for the analysis steps which run in background of the user interface. User can upload gene expression data for constructing consensus GRN. The output obtained from analysis will be available in downloadable form in the result window of the web tool.